1995
DOI: 10.1002/ajhb.1310070405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of religion, economics, and geography on genetic structure of Fogo Island, Newfoundland

Abstract: The population structure of Fogo Island, Newfoundland is described using geography, religious affiliation, economic factors (such as the presence of a fish-packing plant), and genetic markers. Five different analytic methods, R-matrix analysis, r VS. mean per locus heterozygosity, predicted kinship (ϕ), mean first passage time, and Mantel matrix comparisons, were applied to the Fogo Island genetic and demographic data. The results suggest that geography plays a role on Fogo Island in the distribution of genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Crawford, Koertevlyessy, Huntsman, Collins, Duggirala, Martin and Keeping 1995). The analyses of craniofacial variation show that the genetic structure of Northern Ireland is affected by both geographic separation (reflected in variation across birth counties) and religious differences.…”
Section: Discussionmentioning
confidence: 99%
“…Crawford, Koertevlyessy, Huntsman, Collins, Duggirala, Martin and Keeping 1995). The analyses of craniofacial variation show that the genetic structure of Northern Ireland is affected by both geographic separation (reflected in variation across birth counties) and religious differences.…”
Section: Discussionmentioning
confidence: 99%
“…He examined the structures of human populations based on demographic features and standard genetic markers. His research on 10 island villages and outports of Newfoundland provided insight into the roles of religion and geography on the observed genetic variation (Crawford et al, ; Devor, Crawford, & Koertvelyessy, ; Madrigal & Koertvelyessy, , Koertvelyessy & Crawford, ; Koertvelyessy et al, ; Martin et al, ). In the 1980s, Tibor helped organize a demographic study (funded by Earth Watch) of Tiszahat, a subdivided agricultural region of Hungary (Koertvelyessy et al, , Koertvelyessy et al, 1992, Koertvelyessy et al, , Koertvelyessy et al, ).…”
Section: Selected Publications Of Tibor Koertvelyessymentioning
confidence: 99%
“…In the 1980s, Tibor helped organize a demographic study (funded by Earth Watch) of Tiszahat, a subdivided agricultural region of Hungary (Koertvelyessy et al, , Koertvelyessy et al, 1992, Koertvelyessy et al, , Koertvelyessy et al, ). He examined the effects of a shift in the political border of Hungary and Ukraine on the observed migration patterns (Crawford et al, ; Crawford, Koertvelyessy, Pap, Szilagyi, & Duggirala, ; Duggirala, Crawford, & Koertvelyessy, ).…”
Section: Selected Publications Of Tibor Koertvelyessymentioning
confidence: 99%
“…Molecular genetic studies focused on single small isolated communities in Newfoundland may yet identify founder, drift, and inbreeding phenomena on local scales (cf. Bear et al 1987Bear et al , 1988Crawford et al 1995;Martin et al 2000).…”
Section: Mito-nuclear Genome Structure Of Newfoundlandersmentioning
confidence: 99%
“…Throughout the 17th-20th centuries, intermarriage among these diverse settlements was limited by religious, linguistic, socioeconomic, and geographic barriers. Outport communities have typically remained small and isolated, and their progeny remained near the original settlements, such that current regional populations are relatively homogeneous genetically (Crawford et al 1995;Young et al 1999;Martin et al 2000;Parfrey et al 2002). A study of outport populations found that only 1%-8% of the population were immigrants to the area, and that 60% of births were to parents originating from the same community (Bear et al 1987).…”
Section: Introductionmentioning
confidence: 99%